Application of Behavioral Architecture to the Land Layout Configuration of Pre-School and Daycare Center Facilities in Surabaya - Listia, Arnisya Dwi; Hendra, Failasuf Herman; Poedjioetami, Esty (Journal of Civil Engineering, Planning and Design, 2025)
Surabaya, one of Indonesia's major cities, has a high demand for early childhood education facilities, including Pre-School and Daycare Centers. However, many of these facilities are not optimally designed, particularly in supporting social interaction, children's exploration, and the comfort and safety of the learning environment. In the design process, a qualitative descriptive research method was used, involving the collection of primary data through direct field observation, as well as secondary data obtained from online case studies, including references from papers, journals, and books. Based on the analysis, a behavioral architecture approach was applied to the "Adaptive" site planning concept in the design of Pre-School and Daycare Centers in Surabaya. This approach aims to create a learning environment that is more responsive to children's natural behavior in play and learning, thereby supporting their development optimally, safely, and comfortably, dynamically and interactively.